The role of church youth in the transformation agenda of South African cities - Baron, Eugene (HTS teologiese studies, 2017)
The churches in City of Tshwane have incredible youth capital. There is so much energy and passion that fill the concrete walls of the mushrooming churches. This article emerges from a research that was conducted to explore religious innovation and competition amidst demographic and social change among churches in the City of Tshwane. The data of the study suggest that the impetus behind most of the innovation and development in the churches is borne from the hearts and minds of the young people. The striking involvement of the youth in the congregations, their participation and also the reflection in the data in terms of youth agency highlight the concern on their involvement in urban, social change, with specific reference to the City of Tshwane. The article assesses the participation of the church youth in the transformation of the city.